ENHANCING PROBIOTIC AND VITAMIN E SUPPLEMENTATION TO OPTIMIZE GROWTH POTENTIAL IN BROILER CHICKS - Dr. Amara Akhtar, Rasheeka Rasheed, Rohma Talha, Nimra Naseer, Muhammad Munawar Ramzan,; Naila Altaf, Noor Fatima, Irsa Saleem, Saneela Kauser, Muhammad Ahmed Saqib, (Chelonian Research Foundation, 2024)
Consumption of broilers is very high worldwide because broilers are source of protein. Many countries have restricted use of antibiotics for birds and are using probiotics as an alternative source of antibiotics. Probiotics are living microbes which increase immunity and boost growth of birds and other animals Vitamins are among essential nutrients including vitamin E. The research conducted on broiler chicks aimed to evaluate the impact of vitamin E supplementation and probiotics on growth performance and body composition. A total of 21 broiler chicks were divided into three treatment groups. Treatment 1 received a control diet, Treatment 2 was given Protexin probiotics (500 mg/Live), and Treatment 3 received both Protexin probiotics and vitamin E supplement (180 mg/kg). The study spanned 40 days, with weekly measurements taken for parameters such as body weight, weight gain, feed intake, feed conversion ratio (FCR), and specific growth rate (SGR). Analysis of body composition was conducted using various methods. Results indicated that Treatment 3 exhibited the highest significant weight gain, followed by Treatment 2 and then Treatment 1. Treatment 1 had the highest FCR value, while Treatment 3 showed the lowest. Feed intake and SGR were significantly higher in Treatment 3 compared to Treatment 1. Treatment 3 also displayed higher levels of crude protein and ash content compared to Treatment 1. Conversely, Treatment 1 had higher values of crude fat and moisture content compared to Treatment 3. The findings suggest that the combination of vitamin E supplement and Protexin probiotics can effectively enhance the growth performance of broiler chicks. This research contributes valuable insights into optimizing the economic efficiency of broiler production.